Zakat, Barang Tambang, dan Keadilan Sosial di Indonesia - Hasanah, Uswatun (LAW REVIEW, 2011)
Zakah is a pillar of Islam which is closely related to social justice. It is mandatory for every Muslimâs wealth to meet the zakah provision. All new property can be regarded as wealth, if the property meets two conditions, namely, they can be owned and have benefits to be taken out. Based on those principles scholars argue that all property is subject to zakah, including mining products. Zakah is a fundamental principle to uphold the Islamic social structure, since the proper implementation of zakah will reduce the gap between the rich and the poor. For the Islamic people, zakah is obligatory in the economic, social, and moral respect. In economic field, zakah may prevent the accumulation of wealth on a group of wealthy people, whereas in the social, zakah allows the performance of responsibilities of the rich to the poor. As in the moral field, zakah is expected to purify the property owned by Muzakki (zakah payer), and cleanse the soul of the penurious nature and simultaneously purify society from the nature of envy and jealousy. To achieve social justice, economic justice is needed because economic justice is a prerequisite and a complement of social justice. Economic justice and social justice cannot be separated because the economic justice is the basis on which social justice can be upheld. Positive effects of socio-economic aspects included in the zakah, are able to create social justice in society.